2010
DOI: 10.1111/j.1365-2664.2010.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Culling wildlife hosts to control disease: mountain hares, red grouse and louping ill virus

Abstract: Summary1. Culling wildlife hosts is often implemented as a management technique to control pathogen transmission from wildlife to domestic or other economically important animals. However, culling may have unexpected consequences, can be expensive and may have wider implications for biodiversity and ecosystem functioning. 2. We assess the evidence that culling mountain hares Lepus timidus is an effective and practical way to control louping ill virus in red grouse Lagopus lagopus scoticus. 3. Evidence from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Several authors highlighted that culling can affect social behaviour and lead to increased disease transmission whilst fertility control is unlikely to have similar effects (e.g. Smith and Cheeseman 2002;McDonald et al 2008;Killian et al 2009;Harrison et al 2010). In addition, fertility control can induce behavioural changes, such as reproductionrelated long-distance movements, that reduce disease transmission rates (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors highlighted that culling can affect social behaviour and lead to increased disease transmission whilst fertility control is unlikely to have similar effects (e.g. Smith and Cheeseman 2002;McDonald et al 2008;Killian et al 2009;Harrison et al 2010). In addition, fertility control can induce behavioural changes, such as reproductionrelated long-distance movements, that reduce disease transmission rates (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, Harrison et al . ), so the scientific case for culling Mountain Hares is weak (Werritty et al . ).…”
Section: Environmental Impacts Of Management Practicesmentioning
confidence: 99%
“…Estates managed for red grouse in Scotland have cited tick and LIV reductions as one of the reasons for mountain hare culls (Patton et al ., ). A recent review concluded that there was no compelling evidence that hare culls might benefit red grouse when red deer were present (Harrison et al ., ). The current study does not refute this conclusion as it found no relationship to suggest that hare abundance was lower at sites with lower tick burdens or higher rates of grouse breeding success.…”
Section: Discussionmentioning
confidence: 97%